Perinatal mourning: An invisible owner - Pariona-Gutierrez, Evelin Sofia (2023)
In our health system, health personnel only focus on treating pain, solving each case and forgetting the human side of pregnant women and families. A lack of preparation on the part of professionals in perinatal death and mourning is evident, giving rise to avoidance behaviors derived from feelings of incompetence to face these situations. For this reason, specific training of health professionals is necessary on the approach to perinatal grief, emphasizing psychological support for parents and communication behaviors, in addition to the creation of protocols and action guides.